The Strategy of the Educational Institution Ma’arif Nahdlatul Ulama of Central Java In Preventing Radicalism - Ibda, Hamidulloh (Borneo International Journal of Islamic Studies, 2019)
This study aims to describe the strategy of the Education Institution Ma’arif Nahdlatul Ulama of Central Java in preventing radicalism. This research uses descriptive qualitative method with interview and observation techniques. The results of the study, the strategy of the Education Institution Ma’arif Nahdlatul Ulama of Central Java was carried out in several ways. Starting from the strengthening of school quality, ideology, literacy, curriculum, teachers, and school management. Until April 2019, there have been no reports of schools or Islamic School under the Education Institution Ma’arif Nahdlatul Ulama of Central Java that were exposed to or entered into radicalism. For this reason, although this strategy has only been running for one year, it has been effective in preventing radicalism. Despite receiving a positive response and the support of various parties, the Education Institution Ma’arif Nahdlatul Ulama of Central Java itself experienced obstacles and opportunities. With the support of foreign institutions, the government, universities, the strategy of the Education Institution Ma’arif Nahdlatul Ulama of Central Java is optimistic to stem radicalism in schools and Islamic School during a period of management.